2021
DOI: 10.21203/rs.3.rs-293107/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional and Healthy Properties of Yoghurt adding to Green Tea and Coffee Extracts on Reducing Obese and its Complications in Rats

Abstract: The chemical composition and sensory evaluation of yoghurt adding to green tea (GTE) and coffee (GCE) extracts on obese rats were investigated. Ethanol extracts were prepared from green tea and green coffee and their total phenolic compounds and identified phenolic compounds were evaluated. Results showed that the GTE and GCE have highly antioxidant activities. Yoghurt was prepared from low fat buffalo's milk (1.5% fat) blended with 1 % of GTE or GCE. Addition of GTE or GCE had no significant effects on the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Over the storage (1 to 8th day), the decrease in pH was viewed from 5.65 ± 0.06 to 5.55 ± 0.06; however, increase in water activity was from 0.976 ± 0.001 to 0.979 ± 0.002, and this trend was similar as reported in the present study. In corroboration with the current study, Elhassaneen (2021) employed green tea extract in yoghurt and checked its viscosity which was found more in the presence of green tea extract as compared to control. Recently, Mahmood et al (2019) found that incorporation of garlic-like antioxidants in chili sauce at a rate of 10% resulted in increased total soluble solids and viscosity from 33.77 ± 0.06 to 39.90 ± 0.17 °B (18.15%) and 10,539.33 ± 64.58 to 13,271.00 ± 206.21 mPas (20.59%), correspondingly.…”
Section: Storage Stability Attributessupporting
confidence: 86%
“…Over the storage (1 to 8th day), the decrease in pH was viewed from 5.65 ± 0.06 to 5.55 ± 0.06; however, increase in water activity was from 0.976 ± 0.001 to 0.979 ± 0.002, and this trend was similar as reported in the present study. In corroboration with the current study, Elhassaneen (2021) employed green tea extract in yoghurt and checked its viscosity which was found more in the presence of green tea extract as compared to control. Recently, Mahmood et al (2019) found that incorporation of garlic-like antioxidants in chili sauce at a rate of 10% resulted in increased total soluble solids and viscosity from 33.77 ± 0.06 to 39.90 ± 0.17 °B (18.15%) and 10,539.33 ± 64.58 to 13,271.00 ± 206.21 mPas (20.59%), correspondingly.…”
Section: Storage Stability Attributessupporting
confidence: 86%
“…This could be linked to the absence of coffee extract in the samples which could have influenced the colour and general appearance during evaluation and scoring [15]. According to [23] indicated that formation of melanoidins during coffee roasting influences the colour of the coffee brew. This also influenced the appearance of the coffee flavoured yoghurt.…”
Section: E Sensory Analysis Of Yoghurtmentioning
confidence: 99%